Intentional Islanding of Active Distribution Networks by GenSets: An Analysis of Technical Constraints and Opportunities - Edoardo Daccò; Davide Falabretti; Andrea Vicario (International Transactions on Electrical Energy Systems)
The willingness to improve the security and reliability of power supply to end-users, often pushed by prescriptions of national regulatory authorities, is bringing considerable challenges for distribution system operators. Islanding a portion of the public distribution network after a fault is considered a measure to mitigate the effects of service interruptions. This procedure is usually carried out by counterfeeding the grid through a generator set (GenSet). Even if this approach is widely adopted around the world, reenergizing the grid and keeping the electric island stable is not a trivial task. In this framework, the scope of this paper is to provide a set of technical guidelines for the usage of GenSets to supply public grids in emergency conditions. The goal is to highlight the static and dynamic limits of the GenSet operations and simplify their exploitation for the grid operators. The numerical analyses, which have been carried out through the RMS simulation tool of the DigSilent PowerFactory software, also aim to evaluate the technical constraints in the case of active networks, which involve distributed generation implementing regulations according to ENTSO-E and Italian technical standards.